2008
DOI: 10.1111/j.1600-0404.2007.00934.x
|View full text |Cite
|
Sign up to set email alerts
|

Frontal Behavioural Inventory in the differential diagnosis of dementia

Abstract: The FBI is a neurobehavioral tool suitable to distinguish fv-FTD from other forms of dementia also when data from cognitive testing or other behavioral scales fail to support the differential diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 35 publications
2
26
0
2
Order By: Relevance
“…In this study, frontal-related behaviors differentiated subjects with aMCI from early AD, which is compatible with and comparable to previous studies [Milan et al, 2007]. We found that negative behaviors were significantly associated with DTI measurement of the frontal PVWM.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, frontal-related behaviors differentiated subjects with aMCI from early AD, which is compatible with and comparable to previous studies [Milan et al, 2007]. We found that negative behaviors were significantly associated with DTI measurement of the frontal PVWM.…”
Section: Discussionsupporting
confidence: 93%
“…The FBI is a 24-item caregiver-based behavioral questionnaire. It was originally designed for the diagnosis and quantification of frontotemporal dementia symptoms, but is also helpful in the differential diagnosis of dementia [Kertesz, 1997;Milan et al, 2007]. There were four possible response options, resulting in a total score ranging from 0 to 72: (0), mild and occasional (1), moderate (2), or serious and most of the time (3).…”
Section: Executive Function Testsmentioning
confidence: 99%
“…In 2007, Blair et al [15] compared these two scales and stated that FBI discriminated better between different types of FTD In a study on 35 patients with bvFTD, Milan et al [16] also concluded that the FBI was superior to other scales. The FBI appeared to be more specific in detecting personality changes caused by frontal disorders.…”
Section: Relevance Of Npi and Fbi Scales To Establish A Diagnosis Andmentioning
confidence: 99%
“…New alternatives have been developed that aim to replicate daily life activities to enhance ecological validity, such as the Virtual Kitchen Test [71] . Furthermore, since in many patients disease insight is lacking due to frontal dysfunction, behavior changes can be quantified using informant-based questionnaires like the Frontal Behavioural Inventory or the Stereotypy Rating Inventory [72,73] . Krudop …”
Section: Instruments To Measure Frontal Lobe Dysfunctionmentioning
confidence: 99%